Performance Improvement of MIMO-OSTBC System with BCH-TURBO Code In Rayleigh Fading Channel - SOFI Naima; FATIMA Debbat; Fethi Tarik Bendimerad (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Recently, OSTBCs has become a widespread technique for signal transmission over wireless channels because of their diversity gain, but there are not designed to achieve an additional coding gain. Hence, OSTBCs must be concatenated with an external code which allows a significant coding gain.FEC (forward error correction) is a technique used for detecting and possibly correcting errors that can occur when messages are transmitted through a digital communication system, also for rendering the information more reliable. Thus, with staffing these coding techniques that are able to reach Shannon limits, in  MIMO systems, better performances can be achieved by taking advantages of  diversity and coding gains. The objective of this paper is to compare different FEC codes in Rayleigh fading channel and propose an appropriate code for MIMO-OSTBC systems. The simulation results reveal the performance of the proposed model